2010
DOI: 10.1111/j.1600-0579.2009.00587.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Italian dental and dental hygiene students toward tobacco‐use cessation

Abstract: The introduction of a comprehensive tobacco education curriculum in DS and DHS programs could further improve students' perceptions and attitudes and provide knowledge and clinical experience which would lead to the incorporation of TUC into subsequent professional practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 32 publications
(46 reference statements)
8
34
5
Order By: Relevance
“…Dentistry is the ideal profession in influencing patients to quit smoking 10 ( significantly higher among clinical students compared to preclinical students of our sample and is in concurrence with the results of an Italian study conducted among dental and dental hygiene students (Pizzo et al, 2010). The results of this study revealed that the percentage of positive responses to the presence of a relationship between smoking and diseases was higher in final year students of both dental and dental hygiene students compared to entry-level students.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Dentistry is the ideal profession in influencing patients to quit smoking 10 ( significantly higher among clinical students compared to preclinical students of our sample and is in concurrence with the results of an Italian study conducted among dental and dental hygiene students (Pizzo et al, 2010). The results of this study revealed that the percentage of positive responses to the presence of a relationship between smoking and diseases was higher in final year students of both dental and dental hygiene students compared to entry-level students.…”
Section: Discussionsupporting
confidence: 79%
“…The sample was drawn from Kerala University of Health Sciences; India, King Saud University, Al Kharj University and University of Dammam; Saudi Arabia, Ajman University of Science and Technology, and University of Sharjah; United Arab Emirates (UAE) and University of Aden; Yemen. A structured, pre-tested, self-administered 15-item paperand-pencil questionnaire in English language adopted from Carter and Ogden (2007) concerning oral cancer awareness and Pizzo et al (2010) concerning TUC counseling was used. The questionnaire was pre-tested with a group of 10 randomly selected male and female students who were each in their first-or fifth-year to identify any obstacles to its comprehension, and necessary modifications were made accordingly.…”
Section: Methodsmentioning
confidence: 99%
“…Every article was reviewed by two review-behavioral tobacco cessation interventions delivered by dental professionals may increase abstinence rates among cigarette users and smokeless tobacco users. [22][23][24][25][26][27][28][29][30] Information on dental students' perspectives on the provision of tobacco cessation and the perceived barriers associated with such care is necessary in the development and implementation of TDE. [15][16][17][18] A major barrier is a lack of tobacco dependence education (TDE) during dental training.…”
Section: Methodsmentioning
confidence: 99%
“…Quite a few studies have been performed on prevalence of tobacco use and attitudes towards smoking among dental students in various countries [9][10][11][12][13][14]. Among 7 Eastern Mediterranean Region (EMR) countries, whose dental students were studied at a national level utilizing the Global Health Professions Student Survey (GHPSS), the Islamic Republic of Iran had the second lowest prevalence of current cigarette smoking (range from 2% for Libya to 32% for Lebanon) [9].…”
Section: Introductionmentioning
confidence: 99%